Barriers and facilitators of germline genetic evaluation for prostate cancer. Issue 11 (31st May 2021) - Loeb, Stacy; Li, Randall; Sanchez Nolasco, Tatiana; Byrne, Nataliya; Cheng, Heather H.; Becker, Daniel; Leader, Amy E.; Giri, Veda N.
Abstract: Background: Genetic counseling and germline testing have an increasingly important role for patients with prostate cancer (PCa); however, recent data suggests they are underutilized. Our objective was to perform a qualitative study of the barriers and facilitators of germline genetic evaluation among physicians who manage PCa. Methods: We conducted semi‐structured interviews with medical oncologists, radiation oncologists, and urologists from different U.S. practice settings until thematic saturation was achieved at n = 14. The interview guide was based on the Tailored Implementation in Chronic Diseases Framework to identify key determinants of practice. Interview transcripts were independently coded by ≥2 investigators using a constant comparative method. Results: The decision to perform or refer for germline genetic evaluation is affected by factors at multiple levels. Although patient factors sometimes play a role, the dominant themes in the decision to conduct germline genetic evaluation were at the physician and organizational level. Physician knowledge, coordination of care, perceptions of the guidelines, and concerns about cost were most frequently discussed as the main factors affecting utilization of germline genetic evaluation. Conclusions: There are currently numerous barriers to implementation of germline genetic evaluation for PCa. Efforts to expand physician education, to develop tools to enhance genetics in practice, and to facilitate coordination of care surrounding genetic evaluation are important to promote guideline‐concordant care.